Enhancements on Flame Resistance by Inorganic Silicate-Based Intumescent Coating Materials - Sin-Nan Chen (MDPI AG, 2021)
Flame-retardant coatings have drawn much attention in recent years. In this study, an inorganic sodium silicate-based intumescent flame-resistance coating with an excellent flameproof properties is developed by mainly utilizing sodium silicate as the ceramizable binder, via hydrolysis and self-condensation reaction. Fly ash, metakaoline, and wollastonite behave as supplement cementing materials. Major formulation encompasses the combination of the ammonium polyphosphate and pentaerythritol as the flame-retardant additives, and aluminum hydroxide or expandable graphite as the intumescence-improving filler agents. Expandable graphite was found to play an important role in the eventual performance of flame-resistance testing. The results showed that solid interaction forces can be formed between metakaoline and sodium silicate, resulting in a similar material to geopolymer with excellent physical properties. After high-temperature flame testing, a densely complex protective layer of carbon-char created on top of the robust silicon dioxide networks offers notable flame resistance. An optimal ratio in this inorganic intumescent coating contains sodium silicate—metakaoline (weight ratio = 9:1)—ammonium polyphosphate and pentaerythritol, aluminum hydroxide (3, 3, 10 wt.%)—expandable graphite (1 wt.%), which can create 4.7 times higher expansion ratio compared with neat sodium silicate matrix. The results of flame testing demonstrate only 387.1 °C and 506.3 °C on the back surface of steel substrate after one and three hours flaming (>1000 °C) on the other surface, respectively, which could meet the requirements according to the level of fire rating.